2019
DOI: 10.21203/rs.2.17368/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining Trust as a Key Determinant of eHealth Adoption in Malawi

Abstract: The way technology is accepted and utilized may have significant hypothetical and concrete inferences. Thus, eHealth, like any other technology, has little value unless it is used. In this study, fundamental elements influencing consumers’ decision to utilize eHealth services in Malawi were assessed. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) model as the primary model of inference, two new constructs were introduced to determine whether trust is a significant contributor in consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Thus, it reflects that if an individual believes that the doctors/online service providers are trustworthy, honest and are willing to keep their commitment, then the users will be motivated to switch to e-health consultations. These findings are consistent with the previous literature (Gadabu, 2019; Hoque et al , 2016a, 2016b; Luo and Najdawi, 2004). Therefore, it is suggested that online health service providers must focus on building and raising trust with the consumers by offering full support and services as promised.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, it reflects that if an individual believes that the doctors/online service providers are trustworthy, honest and are willing to keep their commitment, then the users will be motivated to switch to e-health consultations. These findings are consistent with the previous literature (Gadabu, 2019; Hoque et al , 2016a, 2016b; Luo and Najdawi, 2004). Therefore, it is suggested that online health service providers must focus on building and raising trust with the consumers by offering full support and services as promised.…”
Section: Discussionsupporting
confidence: 94%